Molecular identification of \(Grateloupia\) and \(Phyllymenia\) (Grateloupiaceae) in Vietnam reveals a new record of \(G. yangjiangensis\) based on \(rbc\)L gene sequences analysis - Nguyen , Nhat Nhu Thuy; Nguyen, Manh Linh; Dam, Duc Tien; Nguyen, Xuan Thuy; Nguyen, Trung Hieu; Dao, Viet Ha; Nguyen, Xuan Vy (Vietnam Journal of Marine Science and Technology, 2024)
Worldwide, the marine macroalgae ‘Grateloupia filicina’ showed several lineages. Among them, Grateloupia filicina is limited to the Mediterranean basin. Previously, several cryptic species were identified as ‘Grateloupia filicina’. In this study, numerous Grateloupia spp. collected from coastal Vietnam and voucher specimens were used for morphological observation and phylogenetic analyses. Both analyses for samples collected at Nha Trang reveal a new record of G. yangjiangensis. The phylogenetic trees indicated that the herbarium vouchers labeled ‘G filicina’ and ‘G. livida’ from other locations of Vietnam group to G. yinggehaiensis clade. In addition, the phylogenetic trees also showed that the unknown Grateloupia sp. recently collected from Cat Ba Island is Phyllymenia taiwanensis. Therefore, a new record, G. yangjiangensis, is added to the Vietnamese flora.